Do researchers collaborate in a similar way to publish and to develop projects?. Issue 1 (February 2019) - Clemente-Gallardo, J.; Ferrer, A.; Íñiguez, D.; Rivero, A.; Ruiz, G.; Tarancón, A.
Highlights: The ways researchers inside an institution collaborate publish a paper together and when they collaborate in a research project are analyzed and compared. The individual productivity of a researcher follows the same laws for the network of research papers and the network of projects. There is a remarkable change in the power laws of productivity when the quality of the papers or projects is considered. There are important structural differences between the two networks. Different areas of knowledge exhibit differences in these behaviors that can be quantified by the properties of the networks. Abstract: The aim of this paper is to establish the similarities and differences between the way of collaboration and the production of researchers when dealing with publications or with the development of projects and whether the collaboration patterns change across disciplines. We have studied the networks of researchers formed through the collaborations in papers or in projects in a research institution (the University of Zaragoza) and we have analyzed a series of individual and global magnitudes. As a general result, we have observed that the laws governing the individual productivity are similar for the cases of publications and projects but, however, the behavior is different when analyzing more complex magnitudes such as the collaborations or other structural variables. We consider also the subnetworks defined by the researchers of the different disciplines and characterize their topologies and compare the corresponding collaboration patterns. Because of the general approach, we expect most of the conclusions to be applicable to other universities or research centers.